West African agriculture and climate change: A comprehensive analysis - Cote d'Ivoire - Ahossane, Kadio; Jalloh, Abdulai; Nelson, Gerald C.; Thomas, Timothy S. (International Food Policy Research Institute, 2012)
The legacy of a decade-long civil war and the projected doubling of the population by 2040–2050 complicate the government’s ability to rebuild the country and to sustainably manage its natural resource base.